Environmental factors influencing the distribution and prevalence of Schistosoma haematobium in school attenders of ILembe and uThungulu Health Districts, KwaZulu-Natal Province, South Africa. Issue 4 (2nd October 2017) - Banhela, Nkosinathi; Taylor, Myra; Gift Zulu, Siphosenkosi; Sund Strabo, Linnea; Floerecke Kjetland, Eyrun; Gunnar Gundersen, Svein
Abstract: Schistosoma haematobium infection is reported to facilitate the development of urogenital diseases. Its symptoms include haematuria, dysuria and tiredness, and it may cause cognitive decline in children. The prevalence of S. haematobium infection needs to be known in endemic areas and a mass treatment programme against the disease implemented. The aim of this study was to investigate the prevalence and intensity of S. haematobium infection in ILembe and uThungulu health districts, using the major symptom, haematuria, as an indicator. A total of 6 265 urine samples, from 96 rural schools, was collected for analysis using dipsticks. The prevalence of haematuria in the ILembe health district was 37% (95% CI, 35–39%) for boys and 39% (95% CI, 37–41%)for girls. The prevalence of haematuria in the uThungulu health district was 56% (95% CI, 53–59%) and 53% (95% CI, 50–56%) for girls and boys, respectively. Light-intensity infection was the most common infection level in both health districts. A negative relationship was observed between prevalence and altitude ( r  = −0.262, p  = 0.009); whereas, we found a slight, though significant, positive association with mid-summer temperatures ( r  = 0.234, p  = 0.021). Associations between prevalence and distance of school to the nearest river were non-significant.